THE EFFECT OF BUDGET PARTICIPATION AND BUDGET EMPHASIS ON BUDGETARY SLACK WITH ENVIRONMENTAL UNCERTAINTY AND TRI HITA KARANA CULTURE AS MODERATING VARIABLES - Jayanti L.S.I.D.; Sujana I K.; Putra I N.W.A.; Badera I D.N. (Russian Journal of Agricultural and Socio-Economic Sciences)
The Regional Revenue and Expenditure Budget (APBD) is used as a tool for planning, controlling, and evaluating, and it functions as a control tool to assess the performance of various accountability units within it. When behaviours emerging from it are positive, the vision and mission of the organization can be achieved according to its goals. However, if individual behaviours are negative, this can lead to the practice of budgetary slack. This study aims to analyze the influence of budget participation and budget emphasis on budgetary slack, considering environmental uncertainty and Tri Hita Karana culture as moderating variables in government agencies (OPD) in Denpasar City. This research adopts a quantitative approach, using primary data from questionnaires. The study was conducted in 36 OPDs in Denpasar City, with a sample size of 128 respondents determined through purposive sampling based on predefined criteria. Data analysis was performed using structural equation modeling (SEM) with SmartPLS 4.0 software. The findings contribute theoretically and practically to minimizing the occurrence of budgetary slack in OPD in Denpasar City. The results indicate that budget participation positively influences budgetary slack, and budget emphasis also positively affects budgetary slack. Environmental uncertainty does not weaken the relationship between budget participation and budgetary slack, and the Tri Hita Karana culture similarly does not weaken this relationship. This study underscores the importance of effective budgetary practices and organizational culture in managing budgetary slack within government agencies, offering insights for both academic understanding and practical application in public financial management.